PENGARUH MOTIVASI KERJA, PENGEMBANGAN KARIR DAN LINGKUNGAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN TERMINAL LPG - Abda Alif (MIX: JURNAL ILMIAH MANAJEMEN, 2015)
Abstrak: The study examines the effect of work motivation, career development, workenvironment on organizational citizenship behavior (OCB) with job satisfaction as interveningvariable. The research approach is a quantitative approach through the method of data collectionusing questionnaires. The sample was totally 158 respondents. Research using analysis ofStructural Equation Model (SEM) that run through AMOS 18.00 software in seeing the influenceof exogenous variables on endogenous variables. The results showed that work motivation in apositive and significant effect on job satisfaction, career development is not a positive andsignificant effect on job satisfaction, work environment in a positive and significant effect on jobsatisfaction, work motivation is not positive and significant effect on organizational citizenshipbehavior, career development is a positive and significant effect on organizational citizenshipbehavior, work environment is not positive and significant effect on organizational citizenshipbehavior, job satisfaction is positively and significantly influence the organizational citizenshipbehavior and work environment through job satisfaction has positive influence on organizationalcitizenship behavior. Other findings are organizational citizenship behavior (OCB) can beincreased due to the work environment, but on the condition that the employees are satisfiedfirst.Keywords: Organizational Citizenship Behavior (OCB), Job Satisfaction, Work Motivation,Career Development, Work Environment.